Informal caregiver burden among carers of bedridden elderly: a cross sectional study in North Kerala - Sajeev, Anjala V.; John, Cyril (International Journal Of Community Medicine And Public Health, 2024)
Background: In the cultural context of India, informal caregiving stands as the foremost form of support to the elderly. This study investigates the status of caregiver burden and it’s psychological impact on informal caregivers of bedridden elderly in rural north Kerala, India. The study also delves into the socio-demographic factors associated with caregiver burden as well as psychological distress among family caregivers. Methods: A cross-sectional descriptive study. The data was collected from (n=120) caregivers using the burden assessment scale and psychological distress assessment scale. Descriptive statistics and inferential statistical tests were employed in this study. Results: The study results reveal that female informal caregivers experience a higher caregiver burden compared to the male counterpart. Most caregivers experience mild to moderate levels of burden and significant levels of stress anxiety and depression. Caregiver burden has a significant difference with the type of relationship with the care recipient and duration of care. Conclusions: This study implies that there is a need for multifaceted interventions to alleviate the caregiver burden and address the psychological manifestations among caregivers.